Isolation of Lactococcus lactis Mutants Simultaneously Resistant to the Cell Wall-Active Bacteriocin Lcn972, Lysozyme, Nisin, and Bacteriophage c2 - Roces, Clara (American Society for Microbiology, 2012)
Lactococcin 972 (Lcn972) is a nonlantibiotic bacteriocin that inhibits cell wall biosynthesis by binding to lipid II. In this work, two mutants resistant to Lcn972, Lactococcus lactis D1 and D1-20, with high (>320 arbitrary units [AU]/ml) and low (80 AU/ml) susceptibilities, respectively, have been isolated. Resistance to Lcn972 did not impose a burden to growth under laboratory conditions, nor did it substantially alter the physicochemical properties of the cell surface. However, the peptidoglycan of the mutants featured a higher content of muropeptides with tripeptide side chains than the wild-type strain, linking for the first time peptidoglycan remodelling to bacteriocin resistance. Moreover, L. lactis lacking a functional d,d-carboxypeptidase DacA (i.e., with a high content of pentapeptide side chain muropeptides) was shown to be more susceptible to Lcn972. Cross-resistance to lysozyme and nisin and enhanced susceptibility to penicillin G and bacitracin was also observed. Intriguingly, the Lcn972-resistant mutants were not infected by the lytic phage c2 and less efficiently infected by phage sk1. Lack of c2 infectivity was linked to a 22.6-kbp chromosomal deletion encompassing the phage receptor protein gene pip. The deletion also included maltose metabolic genes and the two-component system (TCS) F. However, a clear correlation between these genes and resistance to Lcn972 could not be clearly established, pointing to the presence of as-yet-unidentified mutations that account for Lcn972 resistance.